Vibration control of mechanical suspension system using active force control - Mohamad, Maziah; Mailah, Musa; Muhaimin, Abdul Halim (2006)
This paper presents the practical implementation of an active force control (AFC) strategy to a laboratory scaled vibration isolator platform. The research was carried out to investigate the performance of vibration suppression capability of feedback controller using AFC. Two types of controller schemes were examined and compared involving the classic proportionalintegral- derivative (PID) controller and AFC scheme. The laboratory scaled physical rig was developed using the MATLAB/Simulink with Real Time Workshop (RTW) tool that is interfaced with a suitable data acquisition card via a personal computer (PC) as the main controller. Appropriate vibration source was modelled and applied to the proposed systems to test for the system robustness. Results obtained in this study verified the potential and superiority of the proposed AFC scheme as a robust active vibration suppressor compared to the other schemes considered in the study